RehabilitacjaSecond stage of rehabilitation in patients with HeartWare left ventricular support devices - Oleszczyk, Krystian; Zielińska-Meus, Anna; Zielińska, Teresa; Rybicki, Jerzy; Sykosz, Teresa; Żurek, Justyna; Bugajska-Sysiak, Katarzyna; Staroszczyk-Głąb, Weronika; Kurek, Barbara; Szeląg, Anna; Gutkowska, Aurelia; Juda, Lucyna; et al. (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
Background: Implantable ventricular assist devices are one of end-state heart failure treatment methods. They are used as a bridge to transplantation, a bridge to recovery of heart to have time for cardiac regeneration and as a destination therapy. The aim of this study was to assess the second stage of rehabilitation in patients with implantable left ventricular heart devices of the HeartWare type. Methods: 2 patients aged 47 and 63 years underwent a cardiac rehabilitation program: physical exercises and psychotherapy 3 months after implantation of HeartWare devices. A 6-minute walking test was used to assess the results before and after rehabilitation. Aerobic exercises, resistance training and stationary bicycle training were used during rehabilitation. Results: Exercise tolerance and psychological state were improved after rehabilitation.